Self-reported periodisation of nutrition in elite female and male runners and race walkers - Heikura, I. A.; Stellingwerff, T.; Burke, L. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
Athletes should achieve event-specific physiological requirements through careful periodisation of training underpinned by individualised and targeted nutrition strategies. However, evidence of whether, and/or how, elite endurance athletes periodise nutrition is scarce. Accordingly, elite international female (n = 67) and male (n = 37) middle/long-distance athletes (IAAF score:1129 +/- 54; corresponds to 13:22.49 [M] and 15:17.93 [F] in the 5000m) completed an online survey examining self-reported practices of dietary micro, meso and macro periodisation. Data are shown as the percentage of all athletes practicing a given strategy followed by the % of athletes reporting various practices within this self-reported strategy. Differences according to sex, event (middle-distance [800/1500m] vs track-distance [3000-10000m] vs road-distance [marathon/race walks]), calibre (major championship qualifier vs the rest), and training volume (low/moderate/high) were analyzed using Chi-square or Kruskal-Wallis test and indicated statistically different when p.0.05.